Spatiotemporal budgeting of soil erosion in the abandoned fields area of the “Rahnstätter Hof” near Michelbach (Taunus Mts., Western Germany) - Stolz, Christian (ERDKUNDE, 2011)
In the former fields of the abandoned manor “Rahnstätter Hof” in the Lower Taunus Mts. (Rhenish Slate Mts, Rheingau-Taunus-Kreis), it was possible to reconstruct and budget the soil erosion over the last 2,500 years, based on a number of soil profiles studied. Also the rate of colluvial deposition was determined. The interdisciplinary study comprises archaeological findings as well as historical records. The “Rahnstätter Hof” manor of 82 ha of fields, meadows and forests was abandoned in 1870, typical of the phase of abandonment mainly affecting isolated farms of the German Uplands towards the end of the 19th century. The total amount of soil erosion on the former farmland has been calculated to 95,000 tons, 65% of it as sheet erosion, the remaining 27% as gully erosion, leading to the deposition of 7,000 tons of colluvium on and behind field balks and of 42,000 tons of colluvial filling in small valleys. 40% of the eroded material is estimated to have been exported. Soil erosion mainly took place during the Early Modern Era, in response to intensified agriculture by the improved three-field crop rotation system and the overexploitation of forest lands in the pre-industrial era. A gully system studied was found to have developed since Early Medieval times. Soil erosion was found not to have caused the abandonment of the farm, but insufficient productivity in the era of incipient industrialization of farmland located on a north slope. For a better understanding of the land-use history of the presently forested area all relics of human activity in the area were mapped, namely charcoal kiln sites, hollow-ways, field balks, boundary stones and gullies.